TREN-TREN PERGESERAN PEMAKNAAN NASKH DALAM AL-QUR’AN: DARI PENGANULIRAN KE PENUNDAAN - Wardani (Tanzil: Jurnal Studi Al-Quran, 2015)
This article is aimed to explain trends in Moslem scholars’ understanding on abrogation (naskh) theory. The naskh has been commonly conceived as final abrogation of particular Quranic verse by other one. But, this term has transformed from naskh as final abrogation to postponement (nas’). There have been three trends in understanding the naskh as postponement. First, the concept of postponement does not differ basically from the substance of naskh as final abrogation in the sense that both naskh and nas` have same meaning, as the majority of Moslem scholars said. Second, the nas` has own meaning which differs from the naskh, but both are regarded as complementary to each other, as argued by al-Zarkasyī, al-Biqā’ī, and Ibn Āsyūr. Third, the idea that the postponement constitutes an alternative to the naskh as final abrogation, so its proponents, such as Muhammad ‘Abduh and Nashr Hāmid Abū Zayd rejected the naskh as final abrogation and replaced it by the nas’ as postponement.